"NQO1 Gene C609T Polymorphism (dbSNP: rs1800566) and Digestive Tract Cancer Risk: A Meta-Analysis.". (19th May 2018) - Yadav, Upendra; Kumar, Pradeep; Rai, Vandana
ABSTRACT: Several studies reported that polymorphism C609T( rs1800566) in (NAD(P)H): quinoneoxidoreductase 1 ( NQO1 ) gene is associated with risk to digestive tract (DT) cancers, like esophageal cancer (EC), gastric cancer (GC), and colorectal cancer (CRC). Authors conducted a meta-analysis to investigate association between C609T polymorphism and DT cancer risk. Eligible studies were extracted from the databases of PubMed, Google Scholar, Science Direct, and Springer Link. All retrieved articles were evaluated. All statistical analyses were performed using Open Meta-Analyst and MIX1.7 programs. A total of 34 studies including 12, 043 DT cancer cases and 15, 209 healthy controls were included in the present meta- analysis. Results of meta-analysis revealed a significant association between NQO1 C609T polymorphism and DT cancer risk adopting all 5 genetic models (T vs. C: OR = 1.21, 95% CI = 1.11–1.31, p < 0.001; TT vs. CC: OR = 1.48, 95% CI = 1.22–1.79, p < 0.001; TT + CT vs. CC: OR = 1.23, 95% CI = 1.12–1.35, p < 0.001; TT vs. CT + CC: OR = 1.36, 95% CI = 1.15–1.60, p < 0.001; CT vs. CC: OR = 1.16, 95% CI = 1.07–1.27, p < 0.001). In the stratified analysis based on cancer types, significant associations were observed between NQO1 C609T polymorphism and GC (OR = 1.38, 95% CI = 1.11–1.72, p = 0.003) and CRC (OR = 1.18, 95% CI = 1.06–1.30, p = 0.001), but not with EC (OR = 1.16, 95% CI = 0.99–1.35, p = 0.06). Furthermore, stratified analysis based on ethnicity indicated that there was a significant association between NQO1 C609T polymorphism and DT cancer risk in the Asian (TT vs. CC: OR = 1.55, 95% CI = 1.21–2.00, p ≤ 0.001) as well as in Caucasian populations (TT vs. CC: OR = 1.34, 95% CI = 1.04–1.73, p = 0.02). In conclusion, the results of meta-analysis suggested that the NQO1 C609T polymorphism is a risk factor for DT cancers, including GC and CRC.